Mobility Enhancement in Square Quantum Wells: Symmetric Modulation of the Envelop Wave Function - Quang, Doan Nhat; Tung, Nguyen Huyen; Hong, Nguyen Trung; Hai, Tran Thi (Communications in Physics, 2010)
We present a theoretical study of the effects from symmetric modulation of the envelop wave function on quantum transport in square quantum wells (QWs). Within the variational approach we obtain analytic expressions for the carrier distribution and their scattering in symmetric two-side doped square QWs. Roughness-induced scattering are found significantly weaker than those in the asymmetric one-side doped counterpart. Thus, we propose symmetric modulation of the wave function as an efficient method for enhancement of the roughness-limited QW mobility. Our theory is able to well reproduce the recent experimental data about low-temperature transport of electrons and holes in two-side doped square QWs, e.g., the mobility dependence on the channel width, which have not been explained so far